Moderasi Beragama di Indonesia: Perspektif Filsafat Chuang Tzu - Fatlolon, Costantinus (Studia Philosophica et Theologica, 2024)
This article employs an expository-critical approach to Chuang Tzu‟s philosophical concept of equality of things and opinions. Its main purpose is to offer an alternative paradigm for religious moderation in Indonesia. The question that this article addressed is: “What is the relevance of Chuang Tzu‟s concept of the equality of objects and opinions for religious moderation in Indonesia?” This article finds that Chuang Tzu‟s philosophy provides an epistemological and metaphysical basis for religious moderation in Indonesia. Epistemologically, religions are the result of limited human contemplation, construction, and conception dealing with the Infinite Reality. Metaphysically, religions are equal because they originate from one and the same Infinite Reality. This epistemological-metaphysical frame guides different religions in Indonesia to maintain legal-formal commitments regarding the rights and freedoms of every citizen, accept differences and be flexible in religious insights, provide non-violent actions, and respect local wisdom. Finally, this article proposes that all problems that still hinder religious moderation in Indonesia can be solved through a humanist approach to radical religious groups, inter- and intra-religious dialogue, and dialogue between religion and local culture